1962
DOI: 10.1002/asi.5090130208
|View full text |Cite
|
Sign up to set email alerts
|

Secondary publication in cardiovascular, endocrine and psychopharmacologic research

Abstract: In a follow‐up of earlier studies, Biological Abstracts (BA), Chemical Abstracts (CA), Excerpta Medica (EM), Psychological Abstracts (PA) and Current List of Medical Literature (CL) were searched for 240 published articles that resulted from oral research reports given at bio‐medical meetings in 1957 and 1958. Seventy per cent of the 240 papers appeared in at least one of the four abstracting services, and almost 90% were indexed in CL; however, no single abstracting service covered more than about one‐half of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1968
1968
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…We analysed data from 64 studies published in 70 reports [1,3,19-86] (see Additional file 1). Four of those studies were published in two full reports each and with partial overlap of the data [1,45,46,50,51,62,74,84]. Another study was published in three abstracts with substantial redundancy of the reported data [79-81].…”
Section: Resultsmentioning
confidence: 99%
“…We analysed data from 64 studies published in 70 reports [1,3,19-86] (see Additional file 1). Four of those studies were published in two full reports each and with partial overlap of the data [1,45,46,50,51,62,74,84]. Another study was published in three abstracts with substantial redundancy of the reported data [79-81].…”
Section: Resultsmentioning
confidence: 99%
“…They parallel the studies of literature dynamics discussed above. FLEMING and KILGOUR [19], BISHOP and OSBORN [1], BROWN [10], GREGORY [28], HUMMEL [31], KILGOUR [34][35][36][37], MORSE [48], RAISIG [57][58][59][60][61][62], ORR [52][53][54], and STANGL and KILGOUR [65,66] are examples of such studies of biomedical literature dynamics. No doubt these have influenced the concept of »core« collections of biomedical journals, such as those chosen to be initially included in .…”
Section: Introductionmentioning
confidence: 99%